Evidence that a single nucleotide polymorphism in the promoter of the G protein receptor kinase 3 gene is associated with bipolar disorder - Barrett, T B; Hauger, R L; Kennedy, J L; Sadovnick, A D; Remick, R A; Keck, P E; McElroy, S L; Alexander, M; Shaw, S H; Kelsoe, J R (Molecular psychiatry, 2003)
In a genome-wide linkage survey, we have previously shown evidence suggesting that the chromosome 22q12 region contains a susceptibility locus for bipolar disorder (BPD). Two independent family sets yielded lod scores suggestive of linkage at markers in this region near the gene G protein receptor kinase 3 (GRK3). GRK3 is an excellent candidate risk gene for BPD since GRK3 is expressed widely in the brain, and since GRKs play key roles in the homologous desensitization of G protein-coupled receptor signaling. We have also previously shown GRK3 expression to be induced by amphetamine in an animal model of mania using microarray-based expression profiling. To identify possible functional mutations in GRK3, we sequenced the putative promoter region, all 21 exons, and intronic sequence flanking each exon, in 14–22 individuals with BPD. We found six sequence variants in the 5′-UTR/promoter region, but no coding or obvious splice variants. Transmission disequilibrium analyses of one set of 153 families indicated that two of the 5′-UTR/promoter variants are associated with BPD in families of northern European Caucasian ancestry. A supportive trend towards association to one of these two variants (P-5) was then subsequently obtained in an independent sample of 237 families. In the combined sample, the P-5 variant had an estimated allele frequency of 3% in bipolar subjects, and displayed a transmission to non-transmission ratio of 26 : 7.7 ( χ 2 =9.6, one-sided P value=0.0019). Altogether, these data support the hypothesis that a dysregulation in GRK3 expression alters signaling desensitization, and thereby predisposes to the development of BPD.